Pengembangan LKS IPA berorientasi model pembelajaran kuantum materi pesawat sederhana, struktur tumbuhan dan sistem pencernaan untuk siswa kelas VIII SMP - Mitra Sri Rezeki Mitra Sri Rezeki; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2019)
Improving the quality of learning aspects can not be separated from teaching materials and learning models used. Teaching materials that can attract students to learn one of them by using Student Worksheets (LKS). One solution that can be used is developing LKS oriented quantum learning models. This study aims to produce science-based LKS oriented quantum learning models that are valid, practical, and effective so that they can be adjusted by semester 1 VIII grade students. The research conducted included the type of Research and Development (R & D). As object of research, the Science LKS is oriented towards the quantum learning model. The data collection instruments used in this study were: Questionnaire for expert validation, Questionnaire of practicality according to science teacher, Questionnaire of practicality according to students, and sheet of pretest postes on aspects of knowledge. Product analysis techniques and data used are descriptive techniques, graph methods, descriptive statistical analysis, and comparative analysis using t-test.Based on the data analysis that has been done, the results of this study were obtained. First, science-based worksheets oriented to the quantum learning model in class VIII in the first semester of junior high school are in a very valid category with a validity value of 86.12. Second, the science worksheet oriented to this quantum learning model is very practical with 89.84 for the results of the average teacher response and 81.63 for the results of the average student response. Third, the use of scientific approach oriented learning devices is effective in learning which is marked by an increase in the competency of students' natural science students significantly between after and before the use of learning devices at a real level of 5%.